2018
DOI: 10.1016/j.virol.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV related Betacoronavirus and diverse Alphacoronavirus members found in western old-world

Abstract: The emergence of SARS-CoV and MERS-CoV, triggered the discovery of a high diversity of coronaviruses in bats. Studies from Europe have shown that coronaviruses circulate in bats in France but this reflects only a fraction of the whole diversity. In the current study the diversity of coronaviruses circulating in western Europe was extensively explored. Ten alphacoronaviruses in eleven bat species belonging to the Miniopteridae, Vespertilionidae and Rhinolophidae families and, a SARS-CoV-related Betacoronavirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 38 publications
3
79
0
2
Order By: Relevance
“…ruber and H. gigas were found separately, in specific areas of the cave, the same with the other species (M. inflatus and C. afra), except for R. aegyptiacus which was not present in this cave. This spatial segregation could limit direct contact between species and represent a behavioral barrier to interspecific transmission, as previously described for lentiviruses and felids 33,34 and more recently for bats and coronaviruses 32 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…ruber and H. gigas were found separately, in specific areas of the cave, the same with the other species (M. inflatus and C. afra), except for R. aegyptiacus which was not present in this cave. This spatial segregation could limit direct contact between species and represent a behavioral barrier to interspecific transmission, as previously described for lentiviruses and felids 33,34 and more recently for bats and coronaviruses 32 .…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, many studies have described coronaviruses in a wide range of bat species 30,31 . Nevertheless, despite the report of alphacoronaviruses in numerous species of Miniopteridae and Vespertillionidae, Ar Gouilh et al 32 suggested a strict association between Alphacoronavirus EPI6 and Rhinolophidae, a familly usually associated with betacoronaviruses.…”
Section: Discussionmentioning
confidence: 97%
“…However, for most of these strains from countries other than China, only partial RdRp fragment were obtained and full-length genome sequences have been determined for only few of them, thus the available genetic information is insufficient to explore the evolution and spread of these SARSr-CoVs. Phylogeny using these short sequences of currently known SARSr-CoVs indicated that the bat SARSr-CoVs from China are closer to human SARS-CoV than those from other countries (Ar Gouilh et al, 2018;Drexler et al, 2010;Quan et al, 2010;Rihtaric et al, 2010), suggesting Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Bats are considered as the natural reservoir hosts and play a crucial role in transmitting various viruses, including Ebola, Nipah, Coronavirus and others (Cui et al 2019). A high diversity among zoonotic Alphacoronaviruses and SARS-CoV-related Betacoronaviruses has been found in the circulating bats of Western Europe (Gouilh et al 2018). The genetic analyses predict bats as the most probable origin of 2019-nCoV.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%